Chi è Erotion? - Paolucci, Paola (AL. Rivista di studi di Anthologia Latina, 2024)
Abstract Through a careful examination of the epigrammatic cycle dedicated by Martial to Erotion and retrieving information of a juridical and epigraphic nature, news on the identity of Erotion are provided.